Creative tourism research: - Moleiro, Diogo Filipe (2023)
This document analyses the existing literature regarding the creative tourism. Later, based on the results presents new and comprehensive avenues of future research on the topic. Through a bibliometric review, existing research on this theme was analyzed using search keywords in the Scopus and ISI Web of Science databases. After the final selection, the articles were analyzed in terms of keyword co-occurrence using Vosviewer software as an analysis tool. Subsequently, a critical analysis of creative tourism was performed, and finally, possible future research opportunities were proposed. The results show that research on creative tourism gravitates around four major areas that complement each other: creative tourism that occurs through the co-creation of experience; it is based on creativity; it appropriates culture, which can be seen to achieve local sustainability.